Pelatihan Pemetaan Daerah Rawan Bencana Berbasis Teknologi Geospasial bagi Aparatur Desa Suci, Kabupaten Jember - Ana Susiati; Fahmi Arif Kurnianto; Yushardi Yushardi; Imas Tasya Putri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Suci Village is characterized by steep slopes, loamy andosol soils, and land use dominated by settlements and plantations, rendering the area highly vulnerable to natural disasters, particularly flooding. This condition demands capacity building for village officials as local implementers in utilizing geospatial technology to support data-driven disaster mitigation. This community service project aimed to enhance the capacity of Suci Village officials in mapping disaster-prone areas using geospatial technology. A participatory approach was employed, incorporating lecture sessions, hands-on practice with ArcGIS and the InaRISK WebGIS, mentoring, and questionnaire-based pre- and post-training evaluations. The results demonstrated a significant increase in the participants' geospatial comprehension, basic spatial analysis skills, map literacy, and the application of mapping outcomes for decision-making. However, technical mastery of GIS (Geographic Information System) software still requires continued mentorship. These findings indicate that practice-based training using geospatial technology is effective in building the capacity of village officials to produce disaster-prone maps, thereby enabling the determination of appropriate mitigation measures.